LC-NMR Technique in the Analysis of Phytosterols in Natural Extracts - Štěpán Horník; Marie Sajfrtová; Jindřich Karban; Jan Sýkora; Anna Březinová; Zdeněk Wimmer (Journal of Analytical Methods in Chemistry)
The ability of LC-NMR to detect simultaneously free and conjugated phytosterols in natural extracts was tested. The advantages and disadvantages of a gradient HPLC-NMR method were compared to the fast composition screening using SEC-NMR method. Fractions of free and conjugated phytosterols were isolated and analyzed by isocratic HPLC-NMR methods. The results of qualitative and quantitative analyses were in a good agreement with the literature data.